(untitled) (European Journal of Government and Economics, 2026)
This paper advances research on the climate–finance nexus by developing two original composite indices, a Financial Stability Index (FSI) and a Climate Risk Index (CRI), specifically calibrated to Morocco’s climate-vulnerable and bank-based economy. Using annual data spanning 1998 to 2024 and employing a combined VAR and Quantile VAR (QVAR) framework, we provide robust evidence that physical climate risks operate as exogenous drivers of financial instability. The analysis reveals a unidirectional and state-dependent transmission mechanism in which climate shocks exert persistent adverse effects on financial stability, with impacts intensifying by 40% to 60% during periods of financial distress. These findings underscore the necessity of systematically integrating climate risk metrics into macroprudential regulation and offer an empirically grounded framework for strengthening financial resilience in Morocco and comparable water-stressed emerging economies.